A review of the research progress on nursing measures in cardiac rehabilitation with integrated Chinese and western medicine (中西医结合心脏康复护理研究进展) - ZHANG Wenjuan (张文娟); TIAN Hongyan (田洪燕); GEN Ao (耿敖); XU Xiao (徐笑); ZHANG Xuan (张璇); YU Meili (于美丽); YUE Zong (岳宗); CHEN Liang (陈亮) (Association of Integrative Nursing, 2021)
The incidence of cardiovascular disease in China is still showing an increasing trend year by year. The import of the cardiac rehabilitation system can effectively move the prevention and treatment threshold forward, reduce the mortality and disability rate of cardiogenic diseases and the economic cost of the whole society. However, due to the limitations of our country's social support system, traditional concepts, and medical insurance system, the development of cardiac rehabilitation in China is still in its infancy and is facing huge challenges; at the same time, how to integrate Traditional Chinese Medicine into the existing cardiac rehabilitation system, to create a cardiac rehabilitation theory and specific practice with Chinese characteristics is also a hot topic of current research. This article intends to review the application scope of cardiac rehabilitation, nursing theories and innovations in nursing methods of cardiac rehabilitation, with a view to provide a certain degree of clinical improvement of the quality of cardiac rehabilitation, assist the development of cardiac rehabilitation nursing in China, and providing patients with better cardiac rehabilitation services. (我国心血管疾病的发病率仍然呈现逐年升高的趋势, 心脏康复体系的引入能够有效将防治关口前移, 降低心源性疾病的致死率、致残率及全社会的经济负担。但限于我国的社会支持体系、传统观念以及医疗保险体制等多方面的限制, 心脏康复在国内的发展仍然处于起步阶段并且面临着巨大的挑战; 同时, 如何将中医中药整合入现有的心脏康复体系, 打造具有中国特色的心脏康复理论和具体实践, 也是目前研究的热点问题。本文拟就心脏康复的应用范围、护理理论以及心脏康复的护理方法创新等方面进行综述, 以期为临床提高心脏康复质量、助力中国心脏康复护理发展和为患者提供更好的心脏康复服务提供一定的参考依据。)